Studi Deskriptif Gerakan Literasi Sekolah pada Tahap Pembiasaan SDN 24 Kota Bengkulu - Harianto, Kristian; Dalifa; Susanti, Atika (Universitas Bengkulu, 2025)
This research aims to describe the implementation of the School Literacy Movement at SDN 24 Bengkulu City through the habituation stage. The type of research used is descriptive qualitative. The subjects in this research were the principal, 3rd teacher dan students of SDN 24 Bengkulu City. The research instrument uses observation guidelines, interview guidelines and documentation. Data collection techniques used were observation, interviews and documentation. Data analysis of the school literacy movement was carried out by collecting data, condensing data, presenting data, and drawing conclusions. The validity technique used is triangulation and member checking. The research results show, The GLS habituation stage at SDN 24 Bengkulu City, most of the indicators have been implemented and reading activities 15 minutes before lessons have been carried out every day in all subjects, but the School Literacy Team (TLS) has not been found. The conclusion in this research is that the familiarization stage of most of the existing indicators has been implemented.